2020
DOI: 10.3390/plants9040546
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Spectrum, and Stability of Leaf Mutants Induced by Diverse γ-Ray Treatments in Two Cymbidium Hybrids

Abstract: Ionizing radiation combined with in vitro tissue culture has been used for development of new cultivars in diverse crops. The effects of ionizing radiation on mutation induction have been analyzed on several orchid species, including Cymbidium. Limited information is available on the comparison of mutation frequency and spectrum based on phenotypes in Cymbidium species. In addition, the stability of induced chimera mutants in Cymbidium is unknown. In this study, we analyzed the radiation sensitivity, mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Less quantity of chlorophyll (3.02 ± 0.18 μg/mg) and carotenoid (1.19 ± 0.07 μg/mg) compared to the control estimation confirmed the morphological mutation in the M 3 V-4 mutant line [Table 3]. The chlorophyll variegation in leaves after EMS treatment is common to change and seen in different ornamentals, which may be due to the high specificity of EMS for mitochondrial and plastid genome mutations [7,41,42]. Our investigation of improved stomatal density, chlorophyll, and carotenoid contents in the M 3 V-4 mutant line also supports the formation of viridis variegation in the leaf [Figure 12].…”
Section: Evaluation Of Mutants In M 3 Generationmentioning
confidence: 86%
“…Less quantity of chlorophyll (3.02 ± 0.18 μg/mg) and carotenoid (1.19 ± 0.07 μg/mg) compared to the control estimation confirmed the morphological mutation in the M 3 V-4 mutant line [Table 3]. The chlorophyll variegation in leaves after EMS treatment is common to change and seen in different ornamentals, which may be due to the high specificity of EMS for mitochondrial and plastid genome mutations [7,41,42]. Our investigation of improved stomatal density, chlorophyll, and carotenoid contents in the M 3 V-4 mutant line also supports the formation of viridis variegation in the leaf [Figure 12].…”
Section: Evaluation Of Mutants In M 3 Generationmentioning
confidence: 86%
“…It was reported that the treatment of homozygous and heterozygous material affected the mutation frequency and spectrum. In the Cymbidium hybrids RB003 (heterozygosity), the mutation frequency of 50 Gy gamma rays was 0.35%, the mutation effectiveness is calculated as 7 × 10 −5 per dose, which was higher than the homozygous materials [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutagenic effects and mutation characteristics of gamma rays in plants have been particularly important issues concerned by geneticists and breeders. The importance of understanding the relationship between the mutagenesis parameters (such as physical parameters, tissues, sample status, and so on) and the mutation effect is increasingly being recognized [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The main parameters of gamma rays are the total dose and dose rate.…”
Section: Introductionmentioning
confidence: 99%
“…A chimeric common ivy ( H. helix ) sample was collected on Jeju Island. A chimeric plant derived from Cymbidium hybrid ( Cymbidium sinense [♀] × C. goeringii [♂]) was provided by the Advanced Radiation Technology Institute (Jeongeup, Jeollabuk-do, Korea) [ 49 , 50 ]. The chimeric cultivar “Purpureus Variegatus” of Hibicus syriacus was supplied by the National Institute of Forest Science (Suwon, Korea).…”
Section: Methodsmentioning
confidence: 99%